EVALUASI PROGRAM KEWIRAUSAHAAN DESA DAN KOTA DALAM PENGENTASAN PENGANGGURAN - Yuriani, Yuriani; Komariah, Kokom; Sampurno, Yoga Guntur (Jurnal Penelitian Humaniora, 2015)
This study is aimed to describe the condition of inputs, processes, products on the implementation of Rural Entrepreneurship/City Entrepreneurship KWD/KWK, and to obtain information about the program KWD / KWK in helping to solve the unemployment problem through the activity of entrepreneurship in the Special Region of Yogyakarta. This study is categorized as program evaluation research. The research uses survey as the research method. The Evaluation approach uses CIPP (Context, Input, Process and Product), and the Kirkpatrick evaluation model, which includes 4 levels of evaluation, namely the reaction, learning, behavior and result. The results of the evaluation described descriptively. The research is conducted in Yogyakarta. The technique of collecting data uses interviews, questionnaires and documentation. Data analysis was performed with descriptive interpretive techniques. The results illustrate that based on the conditions of context, input and output execution process KWD/KWK generally meets the criteria set by the specified standard, so the quality requirements proposed in the guidelines for the implementation can still be used. Refers to the demands of a set that is 80% of participants are able to get a job or perform entrepreneurial work, the program KWD/new KWK still reaches 74% of participants. However, KWK/KWD is generally considered as a good program to tackle unemployment, it has improved the standard of living of the participants into 34.53%, increase productivity into 64.24%, and increased entrepreneurial attitude into 75%. While detention to perform self- employment can be identified by the participants come from themselves is 60.86%.